Characterization of Poly(vinyl alcohol)/gelatin films made with winery solid by-product (vinasse) extract - Kaynarca, Guelce Bedis; Kamer, Deniz Damla Altan; Gumus, Tuncay; Sagdic, Osman (ELSEVIER, 2023)
The aim of this study is to examine the effect of grape pomace extract (GP) on the technological, functional and structural properties of Poly (vinyl alcohol) (PVA)/fish gelatin (FG) blend films. The addition of different ratios of GP (0 %, 0.5 %, 1 %, 1.5 % and 2 %) to PVA/FG edible films improved their rheological properties. The complex viscosity value increased exponentially when 2 % GP was added to the composite films compared to samples without any added GP. FTIR results showed that PVA and FG were able to interact with GP. The surface morphology indicated that addition of GP enhanced the intermolecular polymer interactions of the PVA-FG-GP combination. Atomic force microscopy (AFM) revealed that the films with GP had homogenous and smoother surfaces. X-ray diffraction (XRD) results confirmed that the FG and PVA chains interacted with GP, causing structural repositioning. Further confirmation of the effective interaction between PVA, FG and GP came from the decrease in crystallinity as the concentration of GP was increased. The melting temperature (Tm) was enhanced with the addition of GP. The combination of GP with PVA/FG films improved the plasticizer and surfactant properties thereby enhancing the flexibility of the films. The water solubility parameter was improved with the addition of GP without compromising the barrier properties. The antioxidant activity of the films increased significantly with the addition of GP. A GP-enriched PVA/FG film can be used as an edible film for food packaging purposes.
Keywords: Fish gelatin; Poly(vinyl alcohol); Grape pomace; Blend film; Texture; BARRIER PROPERTIES; ESSENTIAL OIL; EDIBLE FILMS; ANTIOXIDANT CAPACITY; FORMING SOLUTIONS; CARBON NANOTUBES; COMPOSITE FILMS; SKIN GELATIN; GAS; Food Science & Technology